Analysis of the effectiveness of national renewable energy policies: A case of photovoltaic policies. (November 2017) - Hafeznia, Hamed; Aslani, Alireza; Anwar, Sohail; Yousefjamali, Mahdis
Abstract: Although fossil fuels are the main sources of power generation, they are losing their advantages because of their limitations and environmental and economic concerns. As an alternative, the development of renewable energy technologies is one of the important strategies. Therefore, governments have been encouraging the deployment of renewable energy resources. However, there are gaps between achievements and targets. As most of the national renewable energy development policies are formulated in the entire country equally, the outputs and achievements are different depending on the geographical characteristics, social and economic capabilities of the regions. The purpose of the present study is the analysis and the evaluation of the effectiveness of the equal national renewable energy policy in the different regions of a country. This research focuses on the idea that whether the codification of energy policies according to the local circumstances of each region can result in a greater efficiency of such policies. An innovative framework is presented to categorize the government policies based on the geographical, technical and socio-economic indicators. To examine the presented framework, it is implemented as a case study.